1997
DOI: 10.1097/00007890-199712270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Allograft Nonresponsiveness After Intrathymic Inoculation With Donor Class I Allopeptides

Abstract: We have recently demonstrated that cardiac allograft rejection in the PVG.R8-to-PVG.1U rat strain combination involves the recognition of a isolated class I (RT1.Aa) molecules as peptides in the context of the recipient MHC molecules. Three synthetic peptides (P1, P2, and P3) corresponding to the alpha-helices of the RT1.Aa molecule served as T-cell epitopes for graft rejection. In this study, we demonstrate that two of these peptides (P2 and P3) are sufficient to induce immune nonresponsiveness (median surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Three synthetic RT1.A a peptides corresponding to the regions of disparity in the α1 and α2 domains of the donor and recipient molecules served as efficient CD4 + T‐cell epitopes during graft rejection. Intrathymic inoculation of these peptides under the cover of transient immunosuppression with antilymphocyte serum (ALS) resulted in immune hyporesponsiveness that led to prolonged graft survival (12,13). The state of immune hyporesponsiveness was donor‐specific, dose‐dependent, and effective only when peptides were presented intrathymically, but not systemically (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Three synthetic RT1.A a peptides corresponding to the regions of disparity in the α1 and α2 domains of the donor and recipient molecules served as efficient CD4 + T‐cell epitopes during graft rejection. Intrathymic inoculation of these peptides under the cover of transient immunosuppression with antilymphocyte serum (ALS) resulted in immune hyporesponsiveness that led to prolonged graft survival (12,13). The state of immune hyporesponsiveness was donor‐specific, dose‐dependent, and effective only when peptides were presented intrathymically, but not systemically (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…The immunologically privileged position of the thymus in central tolerance to self makes it a potential site for induction and maintenance of specific tolerance to alloantigens (Ag) since MHC-restricted T-cell recognition of foreign MHC Ag is not an inherent property of the developing T cells but is learned during T-cell maturation (5). Recent studies which show that the deliberate introduction of an alloMHC peptide into the adult thymus induces donor-specific tolerance to cardiac and islet allografts (6)(7)(8)(9)(10) suggest that thymic dendritic cells (DCs) play a pivotal role in acquisition of central tolerance by inducing deletion or functional inactivation of self-reactive immature T cells bearing TCR with high affinity for peptide/MHC molecules present on the surface of thymic DCs (4). We reasoned, therefore, that presentation of allopeptides by self DCs to developing T cells in the thymus might induce acquired thymic tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many studies in rodent models have shown that IT administration of donor alloantigen in various forms, such as spleen cells (28), or MHC allopeptides (29), can induce tolerance to organ allografts.…”
Section: Thymic Injection Of Mhc Antigensmentioning
confidence: 99%